Global priorities of environmental issues to combat food insecurity and biodiversity loss - Scherer, L.; Svenning, Jens Christian; Huang, J.; Seymour, C.; Sandel, B.; Mueller, N.; Kummu, M.; Bekunda, Mateete A.; Bruelheide, H.; Hochman, Z.; Siebert, S.; Rueda, O.; et al. (Elsevier, 2020)
Various environmental challenges are rapidly threatening ecosystems and societies globally. Major interventions and a strategic approach are required to minimize harm and to avoid reaching catastrophic tipping points. Setting evidence-based priorities aids maximizing the impact of the limited resources available for environmental interventions. Focusing on protecting both food security and biodiversity, international experts prioritized major environmental challenges for intervention based on three comprehensive criteria – importance, neglect, and tractability. The top priorities differ between food security and biodiversity. For food security, the top priorities are pollinator loss, soil compaction, and nutrient depletion, and for biodiversity conservation, ocean acidification and land and sea use (especially habitat degradation) are the main concerns. While climate change might be the most pressing environmental challenge and mitigation is clearly off-track, other issues rank higher because of climate change's high attention in research. Research and policy agendas do not yet consistently cover these priorities. Thus, a shift in attention towards the high-priority environmental challenges, identified here, is needed to increase the effectiveness of global environmental protection.